Influence of cutting time interval and season on productivity, nutrient partitioning, and forage quality of blue panicgrass (Panicum antidotale Retz.) under saline irrigation in Southern region of Morocco - El Mouttaqi, Ayoub; Mnaouer, Ihssane; Nilahyane, Abdelaziz; Ashilenje, Dennis S.; Amombo, Erick; Belcaid, Mohamed; Ibourki, Mohamed; Lazaar, Karima; Soulaimani, Aziz; Devkota, Krishna Prasad; Kouisni, Lamfeddal; Hirich, Abdelaziz (Frontiers in Plant Science, 2023)
Salinity has become a major issue in various parts of the world negatively impacting agricultural activities and leading to diminished crop potential and lower yields. Such situation calls for urgent interventions such as adopting salt-tolerant crops to fill the gap in food and feed availability. Blue panicgrass (Panicum antidotale Retz.) is a promising salt-tolerant forage crop that has shown an appropriate adaptation and performance in the saline, arid, and desertic environments of southern Morocco. However, for obtaining a highest forage productivity with nutritional quality, optimization of the cutting interval is required. Thus, the objective of this study was to determine the optimal cutting time interval allowing high forage production and quality under high salinity conditions. This experiment was conducted over one entire year covering the summer and winter seasons. The effect of five cutting time intervals on selected agro-morphological traits, crop productivity, mineral nutrient accumulation, and forage quality of blue panicgrass in the region of Laayoune, southern Morocco. The finding of this study recommend that cutting blue panicgrass every 40 days maximized the annual fresh and dry forage yield as well as the protein yield, which reached 74, 22, and 2.9 t/ha, respectively. This study also revealed a significant effect of the season on both productivity and quality. However, forage yield declined during the winter and increased during the summer, while protein content increased during winter compared to summer. The mineral nutrient partitioning between shoots and roots, especially the K+/Na+ ratio, indicated that blue panicgrass has salt tolerance mechanism as it excluded sodium from the roots and compartmentalized it in the leaves. In conclusion, there is a potential of blue panicgrass on sustaining forage production under salt-affected drylands, as demonstrated by the response to two key questions: (a) a technical question to farmers for its adoption such as at which interval should blue panicgrass be harvested maximizing both forage yield and quality? And (b) a scientific question on how does blue panicgrass maintain high K+/Na+ ratio to cope with salinity stress?